Analisis Efektivitas Pelatihan Sertifikat Kompetensi Mahasiswa FEBI UIN KHAS Jember Terhadap Kesiapan Kerja - Anis Fitriyah; Erlina Nur Nafiah; Zuhriyah Zulian Nihrir; Aldi Dimas Fian Saputra (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study analyzes the effectiveness of competency certification training programs for students of the Faculty of Islamic Economics and Business (FEBI), UIN KHAS Jember, in enhancing their job readiness. Using a qualitative approach and case study design, the research gathered data through interviews, observations, and documentation of training processes and outcomes. The findings reveal that the training significantly improved students' technical skills, self-confidence, and adaptability to workplace dynamics. Moreover, the national certification issued by the National Professional Certification Agency (BNSP) provided added value in terms of industry recognition. The study highlights the strategic role of partnerships with certified training institutions in aligning academic learning with industry demands. It also underscores the need for continuous curriculum updates and institutional support to maximize the training's impact on student career development.